Corporate social irresponsibility & electronic word of mouth : case Volkswagen emissions crisis - Juoperi, Sanni (2017)
Even though corporations’ interest towards corporate social responsibility (CSR) has significantly increased in the last decades, organizations still commit various acts of corporate social irresponsibility (CSI). At the same time the emergence of social media has offered stakeholders interact in ways formerly unimaginable, and the content of these conversations is slipping further away of organizational control. This research participates the theoretical conversations of CSR, CSI and stakeholder research as well as the active stream of social media and electronic word of mouth (eWOM) research.